The Model of a Fiber-Optic Sensor for Monitoring Mechanical Stresses in Mine Workings; Russian Journal of Nondestructive Testing; Vol. 54, iss. 7 - Yurchenko A. V. Aleksey Vasilievich; Mekhtiyev (Mekhtiev) A. Ali; Bulatbaev F. N. Feliks Nazymovich; Neshina E. G. Elena Gennadjevna; Alkina A. D. Aliya Dauletkhanovna (2018, 2018)
Title screen